2012
DOI: 10.1186/1471-2105-13-s13-s11
|View full text |Cite
|
Sign up to set email alerts
|

The Genboree Microbiome Toolset and the analysis of 16S rRNA microbial sequences

Abstract: BackgroundMicrobial metagenomic analyses rely on an increasing number of publicly available tools. Installation, integration, and maintenance of the tools poses significant burden on many researchers and creates a barrier to adoption of microbiome analysis, particularly in translational settings.MethodsTo address this need we have integrated a rich collection of microbiome analysis tools into the Genboree Microbiome Toolset and exposed them to the scientific community using the Software-as-a-Service model via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 23 publications
3
46
0
Order By: Relevance
“…Numerous bioinformatics suites, such as Quantitative Insights into Microbial Ecology (QIIME), Mothur, and Genboree, have been developed specifically to handle the taxonomic information gathered from 16S studies (Schloss et al 2009; Caporaso et al 2010; Riehle et al 2012). These tools streamline the process of quality filtering, operation taxonomic unit (OTU) picking, chimeric sequence removal and taxonomic assignment.…”
Section: Metagenomic Science: Methods Applications and Challenges Imentioning
confidence: 99%
“…Numerous bioinformatics suites, such as Quantitative Insights into Microbial Ecology (QIIME), Mothur, and Genboree, have been developed specifically to handle the taxonomic information gathered from 16S studies (Schloss et al 2009; Caporaso et al 2010; Riehle et al 2012). These tools streamline the process of quality filtering, operation taxonomic unit (OTU) picking, chimeric sequence removal and taxonomic assignment.…”
Section: Metagenomic Science: Methods Applications and Challenges Imentioning
confidence: 99%
“…Several studies have demonstrated the utility of the Boruta algorithm as an efficient technique for feature selection [25], [39], [40] and it has been applied in a number of studies including document indexing [43], microbial metagenomic analyses [44], [45], microarray gene expression studies [46], and forest biodiversity modeling [47]. Reference [47] employed Boruta to determine relevant predictive features for modeling forest species richness.…”
Section: Introductionmentioning
confidence: 99%
“…41 Sequences that had lengths shorter than 200 bp, had average quality scores <20, harbored ambiguous base calls, or had mismatches to their barcode or sequencing primer were excluded from downstream analysis. The quality-filtered sequences were assigned to operational taxonomic units (OTUs, sequences that share ⩾97% similarity) using Cd-Hit.…”
Section: 37mentioning
confidence: 99%